Estudo da solidificação transiente unidirecional na estrutura e dureza das ligas al-2,5%Ni, Al-4%Cu-2,5%Ni, Al-4%Ni e Al-9%Ni - SOUZA, Esaú Gomes (2024)
Many studies have focused on aluminum alloys, which are engineering alloys. The solidification of the material and the way it loses heat has a significant influence on the structure and in turn interferes with the mechanical properties. The present work aims to study the structure and hardness relationship of aluminum alloys of the Al-Cu-Ni and Al-Ni systems obtained by upward unidirectional solidification. Four ingots of the Al- Cu-Ni and Al-Ni systems were manufactured and solidified in an ascending unidirectional transient solidification device with temperature controller, which has a steel ingot mold and isolated electrical resistance with refractory material around it, allowing a favorable environment to extract heat in a single direction. Metallographic analyzes of the alloys, macro and microstructure were carried out with measurement of secondary dendritic spacing (λ2), Scanning Electron Microscopy (SEM). Furthermore, hardness tests were carried out correlating them with the regions of the ingot. The metallographic results showed predominantly columnar structures and dendritic microstructures that are directly influenced by the cooling rate factor as the cooling propagates. The secondary dendritic spacings (λ2) were smaller in the regions close to heat extraction with an average value of 7.86 μm for the R1 region of the Al- 2.5%Ni alloy while in the Al-4%Ni and Al-9% alloys Ni this same region presented average values of 5.89 μm and 4.81 μm, respectively. It is observed that in the regions closest to the base of the heat extraction interface, greater refinement of the structure occurred for all alloys studied in this work. This behavior was due to the heat extraction rates being closer to the base. The literature shows that cooling rates closer to the base are higher and the microstructure behaves in relation to these rates, that is, the higher the cooling rate, the lower the microstructure for this type of solidification. Furthermore, a decrease in hardness was observed in regions further away from the heat extraction interface, this fact occurred due to the increase in dendritic spacing, that is, the smaller the microstructure, the greater the resistance of the material. The alloy strength of the Al-Cu-Ni ternary system showed greater resistance when compared to that of the Al-Ni binary system.